Origin and diversification of Lake Ohrid s endemic acroloxid limpets: the role of geography and ecology - Stelbrink, Björn; Shirokaya, Alena A.; Föller, Kirstin; Wilke, Thomas; Albrecht, Christian; Justus Liebig University Giessen (My University, 2016)
Background: Ancient Lake Ohrid, located on the Albania-Macedonia border, is the most biodiverse freshwater lake in Europe. However, the processes that gave rise to its extraordinary endemic biodiversity, particularly in the species-rich gastropods, are still poorly understood. A suitable model taxon to study speciation processes in Lake Ohrid is the pulmonate snail genus Acroloxus, which comprises two morphologically distinct and ecologically (vertically) separated endemic species. Using a multilocus phylogenetic framework of Acroloxus limpets from the Euro-Mediterranean subregion, together with molecular-clock and phylogeographic analyses of Ohrid taxa, we aimed to infer their geographic origin and the timing of colonization as well as the role of geography and ecology in intra-lacustrine diversification. Results: In contrast to most other endemic invertebrate groups in Lake Ohrid, the phylogenetic relationships of the endemic Ohrid Acroloxus species indicate that the Balkan region probably did not serve as their ancestral area. The inferred monophyly and estimated divergence times further suggest that these freshwater limpets colonized the lake only once and that the onset of intra-lacustrine diversification coincides with the time when the lake reached deep-water conditions ca 1.3 Mya. However, the difference in vertical distribution of these two ecologically distinct species is not reflected in the phylogeographic pattern observed. Instead, western and eastern populations are genetically more distinct, suggesting a horizontal structure. Conclusions: We conclude that both geography and ecology have played a role in the intra-lacustrine speciation process. Given the distinct morphology (sculptured vs. smooth shell) and ecology (littoral vs. sublittoral), and the timing of intra-lacustrine diversification inferred, we propose that the onset of deep-water conditions initially triggered ecological speciation. Subsequent geographic processes then gave rise to the phylogeographic patterns observed today. However, the generally weak genetic differentiation observed suggests incipient speciation, which might be explained by the comparatively young age of the lake system and thus the relatively recent onset of intra-lacustrine diversification.
Keywords: Freshwater limpets; Ancient lakes; Balkans; Molecular phylogen; Molecular clock; ddc:570